Analisis Peluang dan Ancaman dalam Perdagangan Komoditas Perkebunan Teh Indonesia Tahun 2025: Studi Kasus Ekspor ke Malaysia - Eryka Chairunnisa (CV. ITTC INDONESIA, 2026)
Tea trade is an important part of Indonesia’s plantation sector, contributing to non-oil and gas exports, with Malaysia as one of the main export markets. In 2025, national tea production is estimated at approximately 123,961 tons, with exports still dominated by Asian markets, particularly bulk tea for the beverage industry. This study aims to analyze the opportunities and threats in Indonesia’s tea trade to Malaysia using a descriptive quantitative method based on secondary data. The results show that key opportunities arise from strong demand in Malaysia’s beverage industry, geographical proximity, and ASEAN trade integration. Meanwhile, threats include dependence on low value-added bulk tea exports, production fluctuations, and competition from countries such as Vietnam and Kenya. Therefore, strategies to improve quality, diversify products, and strengthen downstream processing are needed to enhance the competitiveness of Indonesia’s tea exports.